Se regrouper, se rendre visibles, s’affirmer : l’expérience des mouvements homosexuels à Genève dans les années 1970 - Sylvie Burgnard (Genre, Sexualité et Société)
This article is based on the history of gay and lesbian groups in Geneva during the seventies. It examines and questions the notion of sexual liberation. In Geneva, homosexual groups emerged in the wake of the dissenting mobilizations of 1968. They accomplish a radical transgression of social norms by breaking isolation, invisibility and guilt. They also struggle against discriminations faced by homosexuals. Although lesbians and gays obviously share a common oppression as a result of the homosexual stigma, gay and lesbian movements nevertheless follow distinct trajectories and only meet on specific occasions.